Recent Advances in Phototrophic Prokaryotes - Hallenbeck, Patrick C. (Advances in Experimental Medicine and Biology,, 2010)
ISPP2009, the 13th International Symposium on Phototrophic Prokaryotes, was held in Montreal, Canada, from August 9 to August 14. This was only the second time that the ISPP series was in North America. ISPP2009 was well attended with about 280 registered participants from over 30 countries. A stimulating and inf- mative program showcased the recent developments in this ever-evolving eld. This is always one of my favourite conference series to attend because not only does it inform my speci c research passions, it broadly educates me in ways that improve my teaching and increase my breadth of understanding in a variety of outside areas. Indeed, the ISPP series brings together a broad spectrum of interests, techniques, and disciplines. Both established researchers and newcomers to this eld gave oral presentations in a large number (80) of plenary and parallel symposia sessions which proved to have active audience participation and lively discussions. A large number of excellent poster presentations supplemented the oral program. I think that the high quality of the scienti c presentations, as well as the enjoyable social events, was widely appreciated. Things ran very smoothly, from the original registration to the closing ceremony, thanks to Isabel Stengler and her team at IS Event Solutions.